Evaluation of Genotoxic Potential of Waters from Two Italian Rivers in Gammarus elvirae (Amphipoda). (1st November 2015) - Ronci, Lucilla; Iannilli, Valentina; De Matthaeis, Elvira; Di Donato, Giovanna; Setini, Andrea
ABSTRACT: : The aim of the present work is to evaluate the genotoxic impact of contaminants along the whole course of Ninfa‐Sisto and Amaseno (Latium, Italy) rivers. The authors performed the alkaline Comet assay to assess DNA damage in the freshwater amphipod Gammarus elvirae, exposed ex situ for 24 hours and 7 days to water collected at different sites. The assay, applied on haemocytes, provides a sensitive tool to reveal effects even at low concentrations of pollutants. The results indicate significant increase of DNA damage along the course of the two rivers, compared to the unpolluted upstream sites, even if the analytes do not exceed the permissible limits. Moreover, the results show that there is not a linear correlation between the concentration of analytes and DNA damage. Based on this study's results, it would be desirable to use Comet assay, on proposed test species, as an early warning method to detect genotoxic potential of waters.